Synthesis and photophysical properties of 1,1′-binaphthol substituted phthalocyanines - Canlica, Mevlude; Nyokong, Tebello (ELSEVIER SCIENCE SA, 2010)
We report on the synthesis, characterization and photophysical properties of a new symmetrically tetra substituted {at non-peripheral positions with tetra(1,1'-bi-binaphtoxy)} phthalocyanines containing H-2, Mg(II), Al(III) Cl, Si(IV)Cl-2 in the central cavity. The synthesized compounds were characterized by the elemental analyses, UV-Vis, FT-IR and H-1 NMR spectroscopies. The fluorescence quantum yields, triplet quantum yields and lifetimes of the newly synthesized H-2, Mg, Al, and Si phthalocyanines were explored. Triplet quantum yields ranged from 0.24 to 0.54. The triplet lifetime for the silicon phthalocyanine derivative was the highest ever reported for a phthalocyanine (similar to 3.5 ms). (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Magnesium; Aluminum; Silicon phthalocyanines; Fluorescence quantum yield; Triplet quantum yield and lifetime; PHOTODYNAMIC THERAPY; ALUMINUM PHTHALOCYANINE; PHOTOSENSITIZERS; ABSORPTION; PORPHYRIN; SILICON; SINGLET; SERIES; Chemistry